Middle East conflicts: Basic features - Janković Slobodan (Međunarodni Problemi, 2007)
The paper explores the causes of the Middle East conflicts. The author considers that apart from historical and religious roots the main causes are the importance of the energy deposits, great and regional powers competition and collisions over energy resources, the complexity of water management in the region for its scarcity, traditional, religious and ethnic differences social differentiations and conflicts, growing poverty among majority of people, demographic problems. The persistence and not solving of these problems clearly indicate that local terrorisms, wars and armed confrontations remain the ominous feature of the region, concludes the author.